Analyses of Genomic tRNA Reveal Presence of Novel tRNAs in Oryza sativa - Mohanta, Tapan K.; Bae, Hanhong (Frontiers in Genetics, 2017)
Transfer rRNAs are important molecules responsible for the translation event during protein synthesis. tRNAs are widespread found in unicellular to multi-cellular organisms. Analysis of tRNA gene family members in Oryza sativa revealed the presence of 750 tRNA genes distributed unevenly in different chromosomes. The length of O. sativa tRNAs were ranged from 66 to 91 nucleotides encoding 52 isoacceptor in total. tRNASer found in chromosome 8 of O. sativa encoded only 66 nucleotides which is the smallest tRNA of O. sativa and to our knowledge, this is the smallest gene of eukaryotic lineage reported so far. Analyses revealed the presence of several novel/pseudo tRNA genes in O. sativa which are reported for the first time. Multiple sequence alignment of tRNAs revealed the presence of family specific conserved consensus sequences. Functional study of these novel tRNA and family specific conserved consensus sequences will be crucial to decipher their importance in biological events. The rate of transition of O. sativa tRNA was found to be higher than the rate of transversion. Evolutionary study revealed, O. sativa tRNAs were evolved from the lineages of multiple common ancestors. Duplication and loss study of tRNAs genes revealed, majority of the O. sativa tRNA were duplicated and 17 of them were found to be undergone loss during the evolution. Orthology and paralogy study showed, the majority of O. sativa tRNA were paralogous and only a few of tRNASer were found to contain orthologous tRNAs.